Transe religioso: uma revisão crítica da produção bibliográfica em Psicologia no Brasil - Ramalho, Thales Barbosa (2016)
The current research aimed to develop a critical analysis and bibliographic survey of the knowledge produced in the scientific literature of the Brazilian Psychology between 2000 and 2015, in what regards religious trance, trance and altered states of consciousness. The analysis purpose was to present when, where, who and how the studies in Psychology regarding religious trance have been conducted. To do so, a search in Brazilian journals of Psychology Qualis A1, A2, B1 and B2 was made from online articles published between 2000 and 2015, indexed on basis of virtual data BVS-Psi, with at least one psychologist author or coauthor. Taking into consideration these standards, the bibliographic review resulted in 17 articles, which were analyzed based on the following analysis categories: (1) Identification Category, (2) Theoretic-Methodologic Category, (3) Content Category. It was possible to observe a majority of psychologist authors (82,60%), with concluded or attending postgraduate education, linked with postgraduate institutions. There was a visible growing movement of publications between the years 2002 and 2010, which stabilized in 2011, but start decreasing in 2012 and 2013, and there were no more publications on the following years of 2014 and 2015. Some themes where recurrent, prevailing articles about religious trance (trance experiences characterization and differential diagnosis between positive religious trance experiences and psychopathological experiences), followed by articles related with the use of trance as a therapeutic tool through hypnosis, altered conscious experiences induced by psychoactive substances, and trance as an innate human potentiality related with aspects of spirituality. It was possible to raise some contributions of these studies for the Clinic Psychology and the psychotherapist work. It was possible to raise some contributions of these studies for the Clinic Psychology and the psychotherapist work, like: 1) the apparent therapeutic effects brought by religious trance experiences (search for health/ cure, insight/ self-knowledge); 2) differences between positive religious trance experiences from disruptive psychopathological experiences; 3) some articulations with theoretical-methodologic thoughts of Psychology, for understanding the meanings behind religious trance experiences; 4) Possible applications of techniques related to trance and conscious alteration in psychotherapy. But the low number of publications, considering the importance of the theme and its possible contributions for the Clinical Psychology, indicate that more studies in Brazil are necessary. (Support by CAPES)